Anxiety, depression and quality of life in dermatology patients at a tertiary care hospital - Hisam, Aliya; Zafar, Hamayal; Akbar , Afnan; Bhatti, Rai Salaar sultan; Hussain , Muhammad Ramis (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the anxiety, depression and health-related quality of life of dermatology patients with healthy individuals in a tertiary care setting. Method: The case-control study was conducted at the Pak-Emirates Military Hospital, Rawalpindi, Pakistan, from April to September 2022, and comprised adult outpatients and inpatients with diagnosed skin diseases. They were designated as group A, while healthy adults who did not suffer from any dermatological condition formed control group B. Data was collected using a questionnaire which in addition to demographic characteristics, comprised the Dermatology Life Quality Index and the Hospital Anxiety and Depression Scale. Data was analysed using SPSS 21. Results: Of the 200 subjects with mean age 30.21±12.09 years, 100(50%) were in group A; 75(75%) males and 25(25%) females with mean age 32.56±13.49 years. The remaining 100(50%) subjects were in group B; 75(75%) males and 25(25%) females with mean age 27.86±10.02. In group A, 71(71%) were outpatients and 29(29%) were inpatients. Quality of life and depression scores were significantly different between inpatients in group A and group B (p<0.05). The difference was significant between outpatients in group A and group B in all categories (p<0.05). Conclusion: Dermatological diseases had a significant impact on the daily life and psychological health of patients. Key Words: Anxiety, Depression, Dermatology, Health-related quality of life, Skin disease.